INTERCONNECTION BETWEEN A CHILD'S SENSORY MOTOR AND SPEECH DEVELOPMENT - Moroz, Liudmyla; Tretjakova, Alla (SWorldJournal, 2025)
The article is devoted to highlighting the problem of the influence of sensory motor development on a child's speech. The authors note that sensory motor development is the basis for the formation of skills necessary for the correct functioning of speech